MnO2@MoS2/RGO hollow structure as high-performance supercapacitor electrode materials. (1st August 2023) - Ran, Jing; Liu, Yafei; Yang, Tiantian; Feng, Huixia; Zhan, Huiying; Shi, Haixiong
Abstract: Reduced graphene (RGO) has garnered substantial attention due to its specific surface area and electrical conductivity as a material for cathodes. However, RGO cannot meet the demand for new energy because of its low capacitance, which has the problem of RGO lamellar agglomeration. Herein, MnO2 @MoS2 /RGO electrode material composite is prepared by using MoS2 /RGO as the conductive substrate and MnO2 as the active substance particles. Electrochemical performance tests showed that the MnO2 @MoS2 /RGO composite electrode has excellent specific capacitance and stable cyclic stability. The prepared nanocomposite material has a capacitance of 743 F g −1 of 1 A g −1, which is greater than that of MnO2 (102 F g −1 ). Specific energy and specific power were 31.22 Whkg −1 and 362.51 Wkg −1 of the MnO2 @MoS2 /RGO material. The cycle stability reaches 88.5 % after 5000 cycles. Due to its excellent electrochemical properties, it has become a hot subject in the research of materials for supercapacitor electrodes. Graphical abstract: Unlabelled Image Highlights: The unique structure, MoS2, and RGO were restructured, to solve the agglomeration problem. Hollow MnO2 nanospheres were synthesized by hydrothermal method on MoS2 /RGO substrate. The type of recombination mechanism was proposed to synthesize MnO2 @MoS2 /RGO electrode material. Eelectrochemical properties, the capacitance of the prepared nanocomposite material is 743 F g −1 at 1 A g −1 .